2013
DOI: 10.1128/mcb.01014-12
|View full text |Cite
|
Sign up to set email alerts
|

Transient JMJD2B-Mediated Reduction of H3K9me3 Levels Improves Reprogramming of Embryonic Stem Cells into Cloned Embryos

Abstract: bCorrect reprogramming of epigenetic marks in the donor nuclei is crucial for successful cloning by nuclear transfer. Specific epigenetic modifications, such as repressive histone lysine methylation marks, are known to be very stable and difficult to reprogram. The discovery of histone lysine demethylases has opened up opportunities to study the effects of removing repressive histone lysine methylation marks in donor cells prior to nuclear transfer. In this study, we generated mouse embryonic stem (ES) cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 54 publications
3
69
1
Order By: Relevance
“…Recent studies have observed that donor cells with decreased H3K9me3 or H3K27me3 levels are associated with improved NT efficiency in cloned embryos (Antony et al 2013, Saini et al 2015, further suggesting that the establishment of accessible chromatin can facilitate nuclear reprogramming in cloned embryos. In this study, we observed that Dnmt3l-KO MEFs display relatively higher levels of H3K27ac and lower levels of H3K9me3 and H3K27me3 compared with WT MEFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have observed that donor cells with decreased H3K9me3 or H3K27me3 levels are associated with improved NT efficiency in cloned embryos (Antony et al 2013, Saini et al 2015, further suggesting that the establishment of accessible chromatin can facilitate nuclear reprogramming in cloned embryos. In this study, we observed that Dnmt3l-KO MEFs display relatively higher levels of H3K27ac and lower levels of H3K9me3 and H3K27me3 compared with WT MEFs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of donor cell with HDACi, trichostatin A (TSA), increases the developmental efficiency and quality of the resulting cloned embryos (Enright et al 2003, Enright et al 2005, Ding et al 2008, suggesting that the initial chromatin status of the somatic cell contributes to the development of the cloned embryo. Furthermore, reduction of the repressive mark H3K9me3 in donor cells also significantly increases cloning efficiency, indicating that the global reduction of the repressive histone modification is beneficial to the onset of reprogramming in cloned embryos (Antony et al 2013. In addition to treatments of donor cells, TSA-treated cloned embryos also displayed lower repressive epigenetic marks, enhanced histone acetylation, remodeling of pericentromeric heterochromatin and increased nascent RNA transcription (Kishigami et al 2006, Rybouchkin et al 2006, Maalouf et al 2009, Bui et al 2010.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Antony et al used mouse stem cell lines to stably overexpress the H3K9 trimethylation (H3K9me3)-specific demethylase KDM4B (JMJD2B) and found that it could significantly increase the blastocyst rate of reconstructed embryos after nuclear transfer. However, they did not investigate the underlying molecular mechanisms further (Antony et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, different types of epigenetic modifications can interact with each other (as shown in Figure 2); the abnormality in one type of epigenetic modification must result in the abnormality in other types of epigenetic modifications. For example, due to incomplete DNA demethylation, cloned embryos would exhibit lower level of histone acetylation and H3K4 methylation, and higher level of H3K9 methylation, that is why treatment of cloned embryos with histone deacetylase inhibitor (trichostatin A, sodium butyrate, Scriptaid, and VPA), as well as inducing express of H3K9me3 demethylases JMJD2B, could improve their developmental ability (Rybouchkin et al 2006;Van Thuan et al 2009;Das et al 2010;Xu et al 2012;Antony et al 2013). …”
Section: Main Barricades Of Reprogramming Somatic Cells By Oocytesmentioning
confidence: 99%